Contralateral Oblique View is Superior to Lateral View for Interlaminar Cervical and Cervicothoracic Epidural Access. Issue 1 (15th September 2014) - Gill, Jatinder S.; Aner, Moris; Jyotsna, Nagda; Keel, John C.; Simopoulos, Thomas T.
Abstract Objective The purpose of this study was to compare the reliability of the lateral fluoroscopic view and several contralateral oblique (CLO) views at different angles in visualizing and accurately predicting the position of the needle tip at the point of access in the posterior cervical and cervicothoracic epidural space. Design After the epidural space was accessed but before confirmation with contrast fluoroscopy, we prospectively obtained fluoroscopic images at eight different angles. Subsequent contrast injection confirmed epidural spread. Needle tip visualization and location of needle relative to bony landmarks were analyzed. Results The needle tip was clearly visualized in all CLO projections in all 24 subjects. CLO view at 50 degrees and at obliquity measured on magnetic resonance imaging (MRI) images provided the most consistent needle tip location. In these views, the epidural space was accessed at or just beyond the ventral laminar margin at the ventral interlaminar line or within the proximal half of the predefined CLO area in all patients. The needle tip was poorly visualized in the lateral view and the location of the needle tip was less well defined and independent of the needle location in the anteroposterior (AP) view. Conclusions This study provides evidence that during cervical and cervicothoracic epidural access, the CLO view at 50 degrees and at MRI‐measured obliquity is superior to the lateral view for the purpose of needle tip visualization and in providing a consistent landmark for accessing the epidural space. This article also introduces the concept of zones to describe needle position in the cervical and cervicothoracic spine in AP, lateral, and oblique views.